Efektifitas Teknik Relaksasi Nafas Dalam dan Pijatan Effleurage terhadap penurunan skala nyeri pada post sectio caesarea - Siti Rochimatul Lailiyah (NHM PRESS, 2019)
Deep breathing relaxation techniques and massagetechniques is an act that can reduce the pain inpostpartum mother sectio caesarea. The purpose ofthis study was to determine the difference in theintensity of post operative pain sectio caesarea withthe technique of deep breathing relaxation andmassage at irna C RSUD Syarifah Ambami RatoEbu Bangkalan. This study uses an experimental quasiapproach. The population is patients who havesevere pain, moderate pain, and mild pain aftersurgery sectio caesarea in irna C RSUD SyarifahAmbami Rato Ebu Bangkalan as many as 57patients. 10-19 year old girls. the sample of 9respondents who taught the technique of deepbreathing relaxation and 9 respondents in givingmassage techniques. sampling technique that isused is probability sampling. Data collection usingSOP and pain scale sheets. Data analysis usingpaired t-test. The results showed that of the 9 respondentsmost respondents after the technique of breathrelaxation in light weight scale as much as 7 (77.8%)postpartum. And from 9 respondents most ofrespondent after done massage technique of lightweight scale as much as 8 (89.9) postpartum.Wilcoxon test results show probability value greaterthan expected significant value (0.317 <0.05). Thismeans there is no difference in the intensity ofpostoperative postoperative pain of caesarea withthe application of deep breathing relaxation andmassage Effleurage. Deep breathing relaxation techniquesand massage techniques are important factors inpreventing the occurrence of severe pain.postpartum is expected to post sectio caesarea tofamiliarize with the technique of deep breathingrelaxation and massage techniques to reduce pain..